2003
DOI: 10.1128/aac.47.7.2242-2248.2003
|View full text |Cite
|
Sign up to set email alerts
|

Plasmid-Mediated Quinolone Resistance in Clinical Isolates of Escherichia coli from Shanghai, China

Abstract: Although quinolone resistance usually results from chromosomal mutations, recent studies indicate that quinolone resistance can also be plasmid mediated. The gene responsible, qnr, is distinct from the known quinolone resistance genes and in previous studies seemed to be restricted to Klebsiella pneumoniae and Escherichia coli isolates from the University of Alabama in Birmingham, where this resistance was discovered. In Shanghai, the frequency of ciprofloxacin resistance in E. coli has exceeded 50% since 1993… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
387
8
12

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 437 publications
(423 citation statements)
references
References 26 publications
11
387
8
12
Order By: Relevance
“…Moreover, this gene was the most common among ESBL producers signifying the relation between this gene and other resistance genes as observed by other researchers [22][23][24][25]. In contrast to the current results, the data reported by Yang et al [3], found that the aac(6′)-Ib-cr gene was the most prevalent among S. marcescens ESBL producers.…”
Section: Discussioncontrasting
confidence: 57%
“…Moreover, this gene was the most common among ESBL producers signifying the relation between this gene and other resistance genes as observed by other researchers [22][23][24][25]. In contrast to the current results, the data reported by Yang et al [3], found that the aac(6′)-Ib-cr gene was the most prevalent among S. marcescens ESBL producers.…”
Section: Discussioncontrasting
confidence: 57%
“…Several reports are available on the mechanism of quinolone resistance in either E.coli or K.pneumoniae or even both or quinolone resistance in ESBL producing bacteria; however, no report is available on the actual resistance of nalidixic acid and ciprofloxacin in these two isolates [29][30][31][32][33][34][35] , except few published studies on urinary isolates, [36][37][38][39][40] whereby low prevalence has been reported as compared to our study. Study performed in our neighboring country reported 17% and 38% of E. coli isolates obtained from uncomplicated and complicated UTI respectively, were found resistant to ciprofloxacin.…”
Section: Quinolone Esbl Resistance and Integronscontrasting
confidence: 48%
“…Transconjugants were screened by double selection method on a Luria-Bertani agar plate containing sodium azide (100 mg l 21 ) and cefotaxime (4 mg l 21 ) or ceftazidime (4 mg l 21 ). Furthermore, aminoglycoside markers were also screened in the presence of sodium azide (100 mg l 21 ) and amikacin (30 mg l 21 ) (Wang et al, 2003). Moreover, susceptibility testing of transconjugants was carried out by disc diffusion and micro-dilution methods.…”
Section: Methodsmentioning
confidence: 99%